Inferring the population structure of the Maghreb sheep breeds using a medium‐density SNP chip - (:unkn) unknown (My University, 2019)
North Africa has a great diversity of indigenous sheep breeds whose origin is linked to its environmental characteristics and to certain historical events that took place in the region. To date, few genome-wide studies have been conducted to investigate the population structure of North African indigenous sheep. The objective of the present study was to provide a detailed assessment of the genetic structure and admixture patterns of six Maghreb sheep populations using the Illumina 50K Ovine BeadChip and comparisons with 22 global populations of sheep and mouflon. Regardless of the method of analysis used, patterns of multiple hybridization events were observed within all North African populations, leading to a heterogeneous genetic architecture that varies according to the breed. The Barbarine population showed the lowest genetic heterogeneity and major southwest Asian ancestry, providing additional support to the Asian origin of the North African fat-tailed sheep. All other breeds presented substantial Merino introgression ranging from 15% for D'man to 31% for Black Thibar. We highlighted several signals of ancestral introgression between North African and southern European sheep. In addition, we identified two opposite gradients of ancestry, southwest Asian and central European, occurring between North Africa and central Europe. Our results provide further evidence of the weak global population structure of sheep resulting from high levels of gene flow among breeds occurring worldwide. At the regional level, signs of recent admixture among North African populations, resulting in a change of the original genomic architecture of minority breeds, were also detected.
Keywords: African Research